MECHANISMS OF YOUTH POLITICAL COMMUNICATION IN VIRTUAL SPACE AND ITS IMPACT ON POLITICAL SUSTAINABILITY: “A THING-INITSELF” OR A FACTOR OF STABILITY? (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The main research goal of the report deals with a comprehensive assessment of themechanisms of youth political communication in the virtual space. The implementation ofthis goal will allow, in turn, to assess the threats and opportunities (positive effects) of suchcommunication on the stability of the socio-political system of a society, to determine thedegree and direction of the possible influence.The study uses both the latest data on the topic (secondary analysis) and own empiricalresearch based on Russian material. The method of empirical research is a personalstandardized interview, the sample size is 1000 respondents who are representatives of youngpeople aged 14 to 30, permanent residents of the studied regions. Within the sampling frame,the distribution by the main indicators is strictly proportional to the official data on averagefor the regions.The relevance of the study seems to be high, since it involves a combination of a fairlycomplete overview of the main directions of research on the role of youth participation in thesocio-political processes and the involvement of specific empirical studies of 2018–2019.At the same time, it is important to understand that in modern political science, one of thesignificant tasks for understanding and predicting the development and sustainability of socioeconomic and political systems is the study of the values and attitudes of future subjects ofpolitical innovations, and young people are in this role.As a result, the study should identify the main mechanisms of political communication,including the most popular sources of political information, fix the main trends in the increaseand decrease in the popularity of specific information sources, analyze the main sociodemographic factors that affect the priority of using certain mechanisms, and also identifythe main channels of political mobilization of youth and the features of their functioning. Thefindings of the ongoing study are to be presented in the report.
Keywords: political communication, youth policy, stability, virtual space, political behavior